(untitled) (Research, Society and Development, 2020)
Objective: To characterize the epidemiological profile of meningitis cases notified in the state of Piauí in 2018. Methodology: Epidemiological study, of a descriptive nature and quantitative approach, whose data were obtained through consultations to the SINAN database (Information System for Notifiable Diseases), made available by the Informatics Department of the Unified Health System (DATASUS). The variables studied were: age group, sex, type of diagnosis, etiologic agent, and notification by municipality. Results: 155 cases of meningitis were reported in the state of Piauí, with the city of Teresina having the highest number of cases (96.13%). As for the age group, subjects aged 20-39 years (25.80%), and male (61.29%), were the most affected by the disease. The majority of reported cases were of unspecified origin (42.58%), followed by viral or aseptic (33.55%) and bacterial (23.87%) meningitis. Conclusion: The study identified a possible underreporting of cases among municipalities in the interior of the state, which suggests greater action by the health system in the sense of conducting frequent epidemiological investigations, with a view to identifying the incidence of cases and whether these are in fact notified. However, regarding diagnostic tests, it was noted that culture, which is the gold standard, needs to be used more by hospital institutions.